High-Risk Markers for Asphyxial Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The value of clinical high-risk markers in detecting neonates having seizures within the first hour of life following intrapartum asphyxia was evaluated in term infants admitted to the neonatal intensive care unit at the University of Texas Southwestern Medical Center, Dallas, TX.